Three-layer composite structure contact material and preparation method thereof

By adopting three-layer composite structural contact material, the high thermal conductivity of the copper diamond layer is used to quickly reduce the arc temperature, which solves the problem of insufficient anti-arc ablation and anti-welding performance of the existing contact materials, achieving higher breaking capacity and service life, and reducing costs.

CN119650327APending Publication Date: 2025-03-18ZHEJIANG METALLURGICAL RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411803359.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

When existing contact materials face the requirements of miniaturization, long life and safety and reliability, their resistance to arc ablation and welding resistance are insufficient, and the quality of graphene is difficult to control and the cost is high, which limits industrialization.

Method used

The three-layer composite structure contact material is used, from bottom to top, which is the copper welding layer, the copper diamond layer and the copper chromium arc burning layer. Only the mixed raw materials of copper and diamond are used in the intermediate layer. It has extremely high thermal conductivity, quickly reduces the temperature of the contact surface layer and arc, and quickly extinguishes the arc.

Benefits of technology

It improves the breaking capacity and service life of the contacts, reduces the area of ​​the molten pool, enhances the anti-fusion welding performance, and avoids graphene quality control problems and high cost problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005178593100000101
    Figure BDA0005178593100000101
Patent Text Reader

Abstract

The invention relates to the field of alloy materials, and discloses a three-layer composite structure contact material and a preparation method thereof. The contact material is of a three-layer composite structure and sequentially comprises a copper welding layer, a copper diamond layer and a copper chromium arcing layer from bottom to top. According to the invention, the mixed raw material of copper and diamond is only adopted in the middle layer, so that the heat conductivity is extremely high, the temperature of the surface layer of the contact and the electric arc can be quickly reduced, the purpose of quickly extinguishing the electric arc is achieved, the breaking capacity and the service life of the contact are improved, and meanwhile, the area of a molten pool can be reduced and the fusion welding resistance of the contact is improved due to the reduction of the temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of alloy materials, and in particular to a three-layer composite structure contact material and a preparation method thereof. Background Art

[0002] As medium and high voltage power switches develop towards miniaturization, long life, safety and reliability, the requirements for core components - contact materials are becoming more stringent, which is manifested in the requirements for smaller and smaller contact sizes, and higher and higher requirements for arc erosion resistance and anti-welding performance.

[0003] To solve the above problems, the currently disclosed solution is to increase the proportion of refractory metals such as tungsten, chromium, molybdenum and other components in the contact material, or to add trace amounts of low-melting-point elements such as tellurium and bismuth that can make the contact matrix brittle. However, both of the above methods have their own disadvantages. Specifically, although the former method can reduce the size of the molten pool and improve the material's resistance to arc ablation, it also reduces the proportion of copper as the main conductive and thermal conductive material in the contact material, which leads to a significant decrease in breaking capacity; although the latter method keeps the proportion of copper basically unchanged and can also reduce the material strength after fusion welding, the low-melting-point elements will form a large amount of metal vapor under the high temperature of the arc during breaking, which makes the switch prone to arc extinguishing failure or reignition after arc extinguishing.

[0004] In recent years, various methods have emerged to add graphene to contact materials to improve the performance of contact materials. However, the quality of graphene is very difficult to control. If it is not properly controlled, it will easily cause the contact performance to deteriorate. In addition, this type of method also has the problem of high cost, which is not conducive to industrialization. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a three-layer composite structure contact material and a preparation method thereof. The contact material of the present invention is a three-layer composite structure, which is divided into a copper welding layer, a copper diamond layer and a copper chromium arc burning layer from bottom to top. The present invention uses a mixed raw material of copper and diamond only in the middle layer, which has extremely high thermal conductivity, can quickly reduce the temperature of the contact surface and the arc, and achieve the purpose of quickly extinguishing the arc, which is beneficial to improving the breaking capacity and service life of the contact. At the same time, the reduction in temperature can reduce the area of ​​the molten pool and improve the anti-welding performance of the contact.

[0006] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a three-layer composite structure contact material, comprising a welding copper layer, a copper diamond layer and a copper chromium arc burning layer stacked in sequence.

[0007] The contact material of the present invention is a three-layer composite structure, which is divided into a copper welding layer, a copper diamond layer and a copper chromium arc burning layer from bottom to top. The copper welding layer is made of pure copper, the copper diamond layer is made of copper and diamond, and the copper chromium arc burning layer is made of copper and chromium.

[0008] When the high-voltage switch is disconnected, an arc will be generated, which will act on the surface of the copper-chromium contact and form a molten pool. Only the surface layer of the contact participates in the generation and extinguishing of the arc, and the internal part only conducts heat and electricity. For this reason, the present invention only uses a mixed raw material of copper and diamond in the middle layer (copper diamond layer), which has extremely high thermal conductivity and can quickly reduce the temperature of the contact surface and the arc, so as to achieve the purpose of quickly extinguishing the arc, which is beneficial to improving the breaking capacity and service life of the contact. At the same time, the reduction in temperature can reduce the area of ​​the molten pool and improve the anti-welding performance of the contact.

[0009] The reason why the present invention does not dope diamond into the copper-chromium arc burning layer is that: on the one hand, the present invention finds that the bonding force between diamond and copper is relatively weak, and it is easy to fall off under the action of mechanical force and electromagnetic field. The fallen diamond powder is distributed in the vacuum switch. At this time, there is a high voltage at both ends of the contact. These powders will reduce the breakdown voltage and form a heavy breakdown, thereby causing arc extinguishing failure; on the other hand, the density of diamond and copper is greatly different. After a molten pool is formed on the surface of the contact under the action of the electric arc, the diamond powder will rise or fall, causing the surface composition of the contact to change, while the density of copper and chromium is small, and the consistency of the composition can be maintained.

[0010] The function of the welding copper layer at the bottom of the contact material of the present invention is to ensure the brazing quality of the contact and other components.

[0011] Preferably, the proportion of chromium in the copper-chromium arcing layer is 25-50wt%.

[0012] Preferably, the proportion of diamond in the copper diamond layer is 10-25wt%.

[0013] The present invention sets the proportion of diamond in the copper-diamond layer within the above range because diamond density is low, and under the same mass proportion, the volume proportion is high. During the research and development process, the present invention found that a diamond-copper composite layer with too high or too low proportion is difficult to prepare, and the thermal expansion coefficient is too different from that of the copper-chromium layer, and is easy to deform.

[0014] Preferably, the overall thickness of the contact material is 3-12 mm; the thickness of the copper-chromium arcing layer is 0.5-1.5 mm; the thickness of the welding copper layer is 0.1-0.3 mm, and the remaining thickness is the copper diamond layer.

[0015] The reason why the thickness of each layer is controlled within the above range in the present invention is that when the vacuum switch is opened, an arc will be formed and act on the surface of the copper-chromium arc burning layer to form a molten pool. The depth of the molten pool is generally less than 0.5 mm, that is, only the surface layer directly participates in the generation and extinction of the arc; the copper-diamond intermediate layer only plays a conductive role, quickly conducts the heat of the surface layer, reduces the surface temperature, and requires a certain thickness to ensure sufficient heat capacity; the role of the welding copper layer is to facilitate the brazing of contacts and other components.

[0016] In a second aspect, the present invention provides a method for preparing the above-mentioned contact material, which specifically comprises the following steps: 1) Electrolytic copper powder and chromium powder having dendritic plasticity are mixed to obtain a mixture A.

[0017] 2) Electrolytic copper powder with dendritic plasticity and diamond powder are mixed by vacuum ball milling to obtain a mixture B.

[0018] 3) Mixture A and mixture B are molded according to the contact material structure to obtain a compact with a loose interior and a porous structure.

[0019] 4) Place the copper sheet into the infiltration mold and place the compact on the surface of the copper sheet with the diamond copper layer facing downward.

[0020] 5) Preheat the infiltration mold in vacuum, pour molten copper into the mold under insulation, infiltrate the chromium matrix and the diamond matrix successively under pressure and weld them with the copper sheet, cool to the aging precipitation temperature, keep warm, and cool rapidly to obtain a three-layer composite structure contact material.

[0021] The key points of the above-mentioned preparation method of the present invention are: (a) Selection of copper source: Mixtures A and B are used as the main raw materials for the copper-chromium arc burning layer and the copper-diamond layer, respectively. The present invention divides the copper source in the copper-chromium arc burning layer and the copper-diamond layer of the contact material into two parts. One part is the electrolytic copper powder in mixtures A and B, and the remaining copper source is provided by the subsequent copper melt. If all electrolytic copper powder is used, it will be difficult to densify and the combination of copper and diamond will be poor. In addition, the present invention finds that the copper source in mixtures A and B is electrolytic copper powder with dendritic plasticity, which can significantly improve the forming performance of brittle chromium powder or diamond powder without adding any binder, and plays an inducing role in the subsequent copper infiltration into the matrix; and the remaining copper source is copper melt, which can infiltrate into the loose porous structure inside the pressed blank under pressure to supplement the copper content of the copper-chromium arc burning layer and the copper diamond layer.

[0022] (b) In step 5), the copper melt needs to be preferentially infiltrated into the chromium matrix of the copper-chromium arcing layer. When the copper melt enters the chromium matrix, a trace amount of chromium will dissolve into the copper melt. These trace amounts of chromium will make it easier for the copper melt to subsequently infiltrate into the diamond matrix (improving the wettability of copper and diamond).

[0023] (c) In step 5), vacuum preheating is first performed to decompose and volatilize some organic impurities in the compact, which is beneficial to the subsequent infiltration. Infiltration by pressurization can make the copper melt better enter the chromium and diamond matrix. Cooling to the aging precipitation temperature and keeping it warm can precipitate the trace chromium dissolved in the copper, thereby improving the electrical and thermal conductivity of the contact.

[0024] Preferably, in 1), the proportion of electrolytic copper powder in the mixture A is 5-15wt%; in 2), the proportion of electrolytic copper powder in the mixture B is 10-20wt%.

[0025] Preferably, in 1), the particle size of the electrolytic copper powder is -200 mesh, and the particle size of the chromium powder is 300-100 mesh; in 2), the particle size of the electrolytic copper powder is -200 mesh, and the particle size of the diamond powder is 600-200 mesh.

[0026] Preferably, in 2), the grinding balls of the ball mill are tungsten balls.

[0027] The reason why the mixture B is mixed by ball milling is that the density of diamond and copper is greatly different, and it is difficult to mix them evenly by conventional mixing methods. The present invention specifically uses tungsten balls as grinding balls. Compared with grinding balls made of other materials, the advantage is that a small amount of tungsten balls will adhere to the surface of diamond during the ball milling process, which can improve the wettability of diamond and copper, facilitate the combination of the two, and make the subsequent infiltration easier.

[0028] More preferably, the diameter of the tungsten ball is 1-5 mm, the ball-to-material ratio is 2-4:1, the ball milling speed is 30-45 rpm, and the time is 120-240 min.

[0029] Preferably, in 5), the vacuum degree of the vacuum preheating is 3-7×10 -2 Pa, temperature is 700-900℃, time is 10-30min.

[0030] Preferably, in 5), the temperature of the copper melt is 1200-1400°C.

[0031] Preferably, in 5), the pressurized pressure is 1-3 MPa.

[0032] Preferably, in 5), the aging precipitation temperature is 450-550°C, and the holding time is 60-120 minutes.

[0033] Compared with the prior art, the beneficial effects of the present invention are: (1) The contact material of the present invention is a three-layer composite structure, which is divided into a copper welding layer, a copper diamond layer and a copper chromium arc burning layer from bottom to top. The present invention uses a mixed raw material of copper and diamond only in the middle layer (copper diamond layer), which has extremely high thermal conductivity and can quickly reduce the temperature of the contact surface and the arc, so as to achieve the purpose of quickly extinguishing the arc, which is beneficial to improving the breaking capacity and service life of the contact. At the same time, the reduction in temperature can reduce the area of ​​the molten pool and improve the anti-welding performance of the contact.

[0034] (2) The present invention divides the copper source in the copper-chromium arc burning layer and the copper-diamond layer of the contact material into two parts. One part is electrolytic copper powder, and the remaining copper source is provided by copper melt. Furthermore, the electrolytic copper powder uses dendritic plastic copper powder, which can significantly improve the forming performance of brittle chromium powder or diamond powder without adding any binder, and plays an inducing role in the subsequent copper infiltration into the matrix; and the remaining copper source uses copper melt, which can infiltrate into the loose porous structure inside the compact under pressure to supplement the copper content of the copper-chromium arc burning layer and the copper diamond layer.

[0035] (3) During the preparation process of the present invention, the copper melt is preferentially infiltrated into the chromium matrix of the copper-chromium arc burning layer. When the copper melt enters the chromium matrix, a trace amount of chromium will dissolve into the copper melt, and this trace amount of chromium will make it easier for the copper melt to subsequently infiltrate into the diamond matrix.

[0036] (4) The present invention preheats the compact in vacuum before infiltrating the molten copper, which can decompose and volatilize some organic impurities in the compact, which is beneficial to the subsequent infiltration. The infiltration is carried out in a pressurized manner, which can make the molten copper better enter the chromium and diamond matrix. Cooling to the aging precipitation temperature and keeping it warm can precipitate the trace chromium dissolved in the copper, thereby improving the electrical and thermal conductivity of the contact. DETAILED DESCRIPTION

[0037] The present invention will be further described below in conjunction with the embodiments.

[0038] Overall embodiment In a first aspect, a three-layer composite structure contact material includes a welding copper layer, a copper diamond layer and a copper chromium arc burning layer stacked in sequence.

[0039] In some preferred implementation cases, the proportion of chromium in the copper-chromium arc burning layer is 25-50wt%; the proportion of diamond in the copper-diamond layer is 10-25wt%.

[0040] In some preferred implementation cases, the overall thickness of the contact material is 3-12 mm; the thickness of the copper-chromium arcing layer is 0.5-1.5 mm; the thickness of the welding copper layer is 0.1-0.3 mm, and the remaining thickness is the copper diamond layer.

[0041] In a second aspect, the method for preparing the contact material comprises the following steps: 1) Electrolytic copper powder and chromium powder having dendritic plasticity are mixed to obtain a mixture A.

[0042] In some preferred implementation cases, in 1), the proportion of electrolytic copper powder in the mixture A is 5-15wt%.

[0043] In some preferred implementation cases, in 1), the particle size of the electrolytic copper powder is -200 mesh, and the particle size of the chromium powder is 300-100 mesh.

[0044] 2) Electrolytic copper powder with dendritic plasticity and diamond powder are mixed by vacuum ball milling to obtain a mixture B.

[0045] In some preferred implementation cases, in 2), the proportion of electrolytic copper powder in the mixture B is 10-20wt%.

[0046] In some preferred implementation cases, in 2), the particle size of the electrolytic copper powder is -200 mesh, and the particle size of the diamond powder is 600-200 mesh.

[0047] In some preferred implementation cases, in 2), the grinding balls of the ball mill are tungsten balls; in some more preferred implementation cases, the diameter of the tungsten balls is 1-5 mm, the ball-to-material ratio is 2-4:1, the ball milling speed is 30-45 rpm, and the time is 120-240 min.

[0048] 3) Mixture A and mixture B are molded according to the contact material structure to obtain a compact with a loose interior and a porous structure.

[0049] 4) Place the copper sheet into the infiltration mold and place the compact on the surface of the copper sheet with the diamond copper layer facing downward.

[0050] 5) Preheat the infiltration mold in vacuum, pour molten copper into the mold under insulation, infiltrate the chromium matrix and the diamond matrix successively under pressure and weld them with the copper sheet, cool to the aging precipitation temperature, keep warm, and cool rapidly to obtain a three-layer composite structure contact material.

[0051] In some preferred implementation cases, in 5), the vacuum degree of the vacuum preheating is 3-7×10 -2 Pa, temperature is 700-900℃, time is 10-30min.

[0052] In some preferred implementation cases, in 5), the temperature of the copper melt is 1200-1400°C.

[0053] In some preferred implementation cases, in 5), the pressurized pressure is 1-3 MPa.

[0054] In some preferred implementation cases, in 5), the aging precipitation temperature is 450-550° C., and the holding time is 60-120 min.

[0055] Specific Examples and Comparative Examples Example 1 Step 1: Take electrolytic copper powder (dendritic plasticity, particle size of 200 mesh) and chromium powder (particle size of 200 mesh) and add them into a three-dimensional mixer for mixing. After mixing evenly, take them out to obtain mixture A (the proportion of electrolytic copper powder is 10wt%).

[0056] Step 2: Take electrolytic copper powder (dendritic plasticity, particle size of 200 mesh), add it and diamond powder (particle size of 400 mesh) into a ball mill, and vacuum it for ball milling mixing; the ball milling ball is a tungsten ball with a diameter of 3 mm, the ball-to-material ratio is 3:1, the ball milling speed is 40 rpm, and the ball milling time is 180 min; after mixing evenly, take out and obtain mixed material B (the proportion of electrolytic copper powder is 15wt%).

[0057] Step 3: Load mixture A into the cemented carbide middle mold, scrape it flat and lift the middle mold to form a new cavity, load mixture B, and then put it into the hydraulic press for limited compression molding. Limited compression molding is used to control the thickness of the contact and calculate the weight of the copper to be infiltrated later. After molding, a compact with a loose porous structure inside is obtained.

[0058] Step 4: Take a piece of oxygen-free copper sheet and put it into the infiltration mold, then put the compact on the oxygen-free copper sheet. Note that the diamond copper layer in the compact is below the copper-chromium arc layer and in contact with the oxygen-free copper sheet.

[0059] Step 5: Place the infiltration mold in step 4 into a vacuum pressure infiltration furnace, close the furnace door, open the pump valve and pump until the vacuum degree is 5×10 -2 Pa, then heated to 900 ° C and kept warm for 20 minutes, then poured 1300 ° C high-temperature copper melt into the infiltration mold, and then pressurized the copper melt in the infiltration mold with a pressure of 2 MPa, so that the copper melt first infiltrates into the chromium matrix, and then infiltrates into the diamond matrix, and is welded to the oxygen-free copper sheet at the bottom, and then cooled with the furnace, cooled to the aging precipitation temperature (500 ° C) and kept warm for 90 minutes, and quickly cooled to obtain a three-layer composite structure contact material.

[0060] The above three-layer composite structure contact material is a sandwich composite structure, including a welding copper layer, a copper diamond layer and a copper chromium arc burning layer stacked in sequence. Among them, the proportion of chromium in the copper chromium arc burning layer is 40wt%, and the proportion of diamond in the copper diamond layer is 15wt%. The overall thickness of the contact material is 8mm, the thickness of the copper chromium arc burning layer is 1mm, the thickness of the welding copper layer is 0.2mm, and the thickness of the copper diamond layer is 6.8mm.

[0061] Example 2 Step 1: Take electrolytic copper powder (dendritic plasticity, particle size of 300 mesh) and chromium powder (particle size of 300 mesh) and add them into a three-dimensional mixer for mixing. After mixing evenly, take them out to obtain mixture A (the proportion of electrolytic copper powder is 15wt%).

[0062] Step 2: Take electrolytic copper powder (dendritic plasticity, particle size of 300 mesh), add it and diamond powder (particle size of 600 mesh) into a ball mill, and vacuum it for ball milling mixing; the ball milling ball is a tungsten ball with a diameter of 5 mm, the ball-to-material ratio is 4:1, the ball milling speed is 45 rpm, and the ball milling time is 240 min; after mixing evenly, take out to obtain mixed material B (the proportion of electrolytic copper powder is 18wt%).

[0063] Step 3: Load mixture A into the cemented carbide middle mold, scrape it flat and lift the middle mold to form a new cavity, load mixture B, and then put it into the hydraulic press for limited compression molding. Limited compression molding is used to control the thickness of the contact and calculate the weight of the copper to be infiltrated later. After molding, a compact with a loose porous structure inside is obtained.

[0064] Step 4: Take a piece of oxygen-free copper sheet and put it into the infiltration mold, then put the compact on the oxygen-free copper sheet. Note that the diamond copper layer in the compact is below the copper-chromium arc layer and in contact with the oxygen-free copper sheet.

[0065] Step 5: Place the infiltration mold in step 4 into a vacuum pressure infiltration furnace, close the furnace door, open the pump valve and pump until the vacuum degree is 3×10 -2 Pa, then heated to 850℃ and kept warm for 30min, then poured 1350℃ high-temperature molten copper into the infiltration mold, and then pressurized the molten copper in the infiltration mold with a pressure of 1.5MPa, so that the molten copper first infiltrates into the chromium matrix, and then infiltrates into the diamond matrix, and is welded to the oxygen-free copper sheet at the bottom, and then cooled with the furnace, cooled to the aging precipitation temperature (550℃) and kept warm for 60min, and quickly cooled to obtain a three-layer composite structure contact material.

[0066] The above three-layer composite structure contact material is a sandwich composite structure, including a welding copper layer, a copper diamond layer and a copper chromium arc burning layer stacked in sequence. Among them, the proportion of chromium in the copper chromium arc burning layer is 50wt%, and the proportion of diamond in the copper diamond layer is 20wt%. The overall thickness of the contact material is 4mm, the thickness of the copper chromium arc burning layer is 0.8mm, the thickness of the welding copper layer is 0.2mm, and the thickness of the copper diamond layer is 3mm.

[0067] Example 3 Step 1: Take electrolytic copper powder (dendritic plasticity, particle size of 250 mesh) and chromium powder (particle size of 120 mesh) and add them into a three-dimensional mixer for mixing. After mixing evenly, take them out to obtain mixture A (the proportion of electrolytic copper powder is 7wt%).

[0068] Step 2: Take electrolytic copper powder (dendritic plasticity, particle size of 250 mesh), add it and diamond powder (particle size of 200 mesh) into a ball mill, and vacuum it for ball milling mixing; the ball milling ball is a tungsten ball with a diameter of 1 mm, the ball-to-material ratio is 3:1, the ball milling speed is 42 rpm, and the ball milling time is 120 min; after mixing evenly, take out to obtain mixed material B (the proportion of electrolytic copper powder is 12wt%).

[0069] Step 3: Load mixture A into the cemented carbide middle mold, scrape it flat and lift the middle mold to form a new cavity, load mixture B, and then put it into the hydraulic press for limited compression molding. Limited compression molding is used to control the thickness of the contact and calculate the weight of the copper to be infiltrated later. After molding, a compact with a loose porous structure inside is obtained.

[0070] Step 4: Take a piece of oxygen-free copper sheet and put it into the infiltration mold, then put the compact on the oxygen-free copper sheet. Note that the diamond copper layer in the compact is below the copper-chromium arc layer and in contact with the oxygen-free copper sheet.

[0071] Step 5: Place the infiltration mold in step 4 into a vacuum pressure infiltration furnace, close the furnace door, open the pump valve and pump until the vacuum degree is 6×10 -2 Pa, then heated to 800 ° C and kept warm for 30 minutes, then poured into the infiltration mold a high-temperature copper melt of 1400 ° C, and then pressurized the copper melt in the infiltration mold with a pressure of 3 MPa, so that the copper melt first infiltrates into the chromium matrix, and then infiltrates into the diamond matrix, and is welded to the oxygen-free copper sheet at the bottom, and then cooled with the furnace, cooled to the aging precipitation temperature (480 ° C) and kept warm for 120 minutes, and quickly cooled to obtain a three-layer composite structure contact material.

[0072] The above three-layer composite structure contact material is a sandwich composite structure, including a welding copper layer, a copper diamond layer and a copper chromium arc burning layer stacked in sequence. Among them, the proportion of chromium in the copper chromium arc burning layer is 30wt%, and the proportion of diamond in the copper diamond layer is 10wt%. The overall thickness of the contact material is 12mm, the thickness of the copper chromium arc burning layer is 1.5mm, the thickness of the welding copper layer is 0.3mm, and the thickness of the copper diamond layer is 10.2mm.

[0073] Comparative Example 1 (Compared with Example 1, the only difference is that the mixed powder sintering method is directly adopted instead of the compacting infiltration method) Step 1: Take electrolytic copper powder (dendritic plasticity, particle size of 200 mesh) and chromium powder (particle size of 200 mesh) and add them into a three-dimensional mixer for mixing. After mixing evenly, take them out to obtain mixture A (the proportion of electrolytic copper powder is 60wt%).

[0074] Step 2: Take electrolytic copper powder (dendritic plasticity, particle size of 200 mesh), add it and diamond powder (particle size of 400 mesh) into a ball mill, and vacuum it for ball milling mixing; the ball milling ball is a tungsten ball with a diameter of 3 mm, the ball-to-material ratio is 3:1, the ball milling speed is 40 rpm, and the ball milling time is 180 min; after mixing evenly, take out and obtain mixed material B (the proportion of electrolytic copper powder is 85wt%).

[0075] Step 3: Load the electrolytic copper powder (dendritic plasticity, particle size of 200 mesh) into the cemented carbide middle mold, scrape it flat and lift the middle mold to form a cavity, then load the mixture A into the cemented carbide middle mold, scrape it flat and lift the middle mold to form a new cavity, load the mixture B, and then put it into the hydraulic press for compression molding. The compression pressure is 1500MPa to obtain a three-layer composite compact.

[0076] Step 4: Place the above compact into a vacuum sintering furnace for sintering at a sintering temperature of 950°C. Keep the temperature for 150 minutes and then cool it down. When the temperature drops to 500°C, keep the temperature for 90 minutes and cool it quickly to obtain a three-layer composite structure contact material.

[0077] Comparative Example 2 (Compared with Example 1, the only difference is that no welding layer is designed, and the copper solution first melts and infiltrates into the diamond and then into the chromium) Step 1: Take electrolytic copper powder (dendritic plasticity, particle size of 200 mesh) and chromium powder (particle size of 200 mesh) and add them into a three-dimensional mixer for mixing. After mixing evenly, take them out to obtain mixture A (the proportion of electrolytic copper powder is 10wt%).

[0078] Step 2: Take electrolytic copper powder (dendritic plasticity, particle size of 200 mesh), add it and diamond powder (particle size of 400 mesh) into a ball mill, and vacuum it for ball milling mixing; the ball milling ball is a tungsten ball with a diameter of 3 mm, the ball-to-material ratio is 3:1, the ball milling speed is 40 rpm, and the ball milling time is 180 min; after mixing evenly, take out and obtain mixed material B (the proportion of electrolytic copper powder is 15wt%).

[0079] Step 3: Load mixture A into the cemented carbide middle mold, scrape it flat and lift the middle mold to form a new cavity, load mixture B, and then put it into the hydraulic press for limited compression molding. Limited compression molding is used to control the thickness of the contact and calculate the weight of the copper to be infiltrated later. After molding, a compact with a loose porous structure inside is obtained.

[0080] Step 4: Place the compact in the infiltration mold, making sure that the diamond copper layer in the compact is above the copper chromium arcing layer.

[0081] Step 5: Place the infiltration mold in step 4 into a vacuum pressure infiltration furnace, close the furnace door, open the pump valve and pump until the vacuum degree is 5×10 -2 Pa, then heated to 900℃ and kept warm for 20min, then poured 1300℃ high-temperature molten copper into the infiltration mold, and then pressurized infiltration was performed on the molten copper in the infiltration mold, the pressurized pressure was 2MPa, and then cooled with the furnace after infiltration, cooled to the aging precipitation temperature (500℃) and kept warm for 90min, and quickly cooled to obtain a double-layer composite structure contact material.

[0082] Comparative Example 3 (Compared with Example 1, the only difference is that the pressure infiltration method is not used) Step 1: Take electrolytic copper powder (dendritic plasticity, particle size of 200 mesh) and chromium powder (particle size of 200 mesh) and add them into a three-dimensional mixer for mixing. After mixing evenly, take them out to obtain mixture A (the proportion of electrolytic copper powder is 10wt%).

[0083] Step 2: Take electrolytic copper powder (dendritic plasticity, particle size of 200 mesh), add it and diamond powder (particle size of 400 mesh) into a ball mill, and vacuum it for ball milling mixing; the ball milling ball is a tungsten ball with a diameter of 3 mm, the ball-to-material ratio is 3:1, the ball milling speed is 40 rpm, and the ball milling time is 180 min; after mixing evenly, take out and obtain mixed material B (the proportion of electrolytic copper powder is 15wt%).

[0084] Step 3: Load mixture A into the cemented carbide middle mold, scrape it flat and lift the middle mold to form a new cavity, load mixture B, and then put it into the hydraulic press for limited compression molding. Limited compression molding is used to control the thickness of the contact and calculate the weight of the copper to be infiltrated later. After molding, a compact with a loose porous structure inside is obtained.

[0085] Step 4: Take a piece of oxygen-free copper sheet and put it into the infiltration mold, then put the compact on the oxygen-free copper sheet. Note that the diamond copper layer in the compact is below the copper-chromium arc layer and in contact with the oxygen-free copper sheet.

[0086] Step 5: Place the infiltration mold in step 4 into a vacuum pressure infiltration furnace, close the furnace door, open the pump valve and pump until the vacuum degree is 5×10 -2 Pa, then heat to 900℃ and keep warm for 20min, then pour 1300℃ high-temperature molten copper into the infiltration mold to make the molten copper directly cover the pressed billet, keep warm for 15min and cool with the furnace, cool to the aging precipitation temperature (500℃) and keep warm for 90min, quickly cool to room temperature and take out.

[0087] Comparative Example 4 (Compared with Example 1, the only difference is that no electrolytic copper powder is used, and a binder paraffin is used) Step 1: Take paraffin powder (particle size of 1000 mesh) and chromium powder (particle size of 200 mesh) and add them into a three-dimensional mixer for mixing. After mixing evenly, take them out to obtain a mixture A (paraffin accounts for 3wt%).

[0088] Step 2: Take paraffin powder (particle size of 1000 mesh) and diamond powder (particle size of 400 mesh) and add them into a ball mill, and vacuum them for ball milling; the ball milling balls are tungsten balls with a diameter of 3 mm, the ball-to-material ratio is 3:1, the ball milling speed is 40 rpm, and the ball milling time is 180 min; after mixing evenly, take out and obtain mixed material B (paraffin accounts for 5 wt%).

[0089] Step 3: Load mixture A into the cemented carbide middle mold, scrape it flat and lift the middle mold to form a new cavity, load mixture B, and then put it into the hydraulic press for limited compression molding. Limited compression molding is used to control the thickness of the contact and calculate the weight of the copper to be infiltrated later. After molding, a compact with a loose porous structure inside is obtained.

[0090] Step 4: Take a piece of oxygen-free copper sheet and put it into the infiltration mold, then put the compact on the oxygen-free copper sheet. Note that the diamond copper layer in the compact is below the copper-chromium arc layer and in contact with the oxygen-free copper sheet.

[0091] Step 5: Place the infiltration mold in step 4 into a vacuum pressure infiltration furnace, close the furnace door, open the pump valve and pump until the vacuum degree is 5×10 -2 Pa, then heated to 900 ° C and kept warm for 20 minutes, then poured 1300 ° C high-temperature copper melt into the infiltration mold, and then pressurized the copper melt in the infiltration mold with a pressure of 2 MPa, so that the copper melt first infiltrates into the chromium matrix, and then infiltrates into the diamond matrix, and is welded to the oxygen-free copper sheet at the bottom, and then cooled with the furnace, cooled to the aging precipitation temperature (500 ° C) and kept warm for 90 minutes, and quickly cooled to obtain a three-layer composite structure contact material.

[0092] Comparative Example 5 (Compared with Example 1, the only difference is that the grinding beads of the ball mill do not use tungsten balls) Step 1: Take electrolytic copper powder (dendritic plasticity, particle size of 200 mesh) and chromium powder (particle size of 200 mesh) and add them into a three-dimensional mixer for mixing. After mixing evenly, take them out to obtain mixture A (the proportion of electrolytic copper powder is 10wt%).

[0093] Step 2: Take electrolytic copper powder (dendritic plasticity, particle size of 200 mesh), add it and diamond powder (particle size of 400 mesh) into a ball mill, and vacuum it for ball milling mixing; the ball milling balls are steel balls with a diameter of 3 mm, the ball-to-material ratio is 3:1, the ball milling speed is 40 rpm, and the ball milling time is 180 min; after mixing evenly, take out to obtain mixed material B (the proportion of electrolytic copper powder is 15wt%).

[0094] Step 3: Load mixture A into the cemented carbide middle mold, scrape it flat and lift the middle mold to form a new cavity, load mixture B, and then put it into the hydraulic press for limited compression molding. Limited compression molding is used to control the thickness of the contact and calculate the weight of the copper to be infiltrated later. After molding, a compact with a loose porous structure inside is obtained.

[0095] Step 4: Take a piece of oxygen-free copper sheet and put it into the infiltration mold, then put the compact on the oxygen-free copper sheet. Note that the diamond copper layer in the compact is below the copper-chromium arc layer and in contact with the oxygen-free copper sheet.

[0096] Step 5: Place the infiltration mold in step 4 into a vacuum pressure infiltration furnace, close the furnace door, open the pump valve and pump until the vacuum degree is 5×10 -2 Pa, then heated to 900 ° C and kept warm for 20 minutes, then poured 1300 ° C high-temperature copper melt into the infiltration mold, and then pressurized the copper melt in the infiltration mold with a pressure of 2 MPa, so that the copper melt first infiltrates into the chromium matrix, and then infiltrates into the diamond matrix, and is welded to the oxygen-free copper sheet at the bottom, and then cooled with the furnace, cooled to the aging precipitation temperature (500 ° C) and kept warm for 90 minutes, and quickly cooled to obtain a three-layer composite structure contact material.

[0097] Performance Testing Various performance tests were performed on the contact materials obtained in the above embodiments and comparative examples, and the results are shown in the following table.

[0098] From the comparison of the data in the above table, it can be seen that: the material prepared by the conventional pressing and sintering method in Comparative Example 1 has the disadvantage of low density, so the electrical and thermal conductivity is poor; there is a melt infiltration sequence in Comparative Example 2, the diamond copper layer is first melt-infiltrated, no small amount of chromium is dissolved in copper, the wettability of diamond and copper is poor, so the density is low and the performance is poor, and no brazing layer is designed, and the weldability is poor; Comparative Example 3 is melt-infiltrated under a pressureless state, the copper solution does not enter the diamond, so the composite contact material cannot be prepared; Comparative Example 4 does not add induced copper, so the density is relatively low, and the electrical and thermal conductivity is also relatively poor; Comparative Example 5 uses steel balls for ball milling, and there is no tungsten element to improve the wettability of diamond and copper, so the melt infiltration effect is poor and the density of the diamond copper layer is low.

[0099] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0100] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A three-layer composite structure contact material, characterized in that: It includes a welding copper layer, a copper diamond layer and a copper chromium arc burning layer which are stacked in sequence; The proportion of chromium in the copper-chromium arc burning layer is 25-50wt%; The proportion of diamond in the copper diamond layer is 10-25wt%.

2. The contact material according to claim 1, characterized in that: The overall thickness of the contact material is 3-12 mm; The thickness of the copper-chromium arc burning layer is 0.5-1.5 mm; The thickness of the welding copper layer is 0.1-0.3 mm.

3. A method for preparing the contact material according to claim 1 or 2, characterized in that include: 1) Mix the dendritic plastic electrolytic copper powder and chromium powder to obtain a mixture A; 2) ball-milling the dendritic plastic electrolytic copper powder and diamond powder to obtain a mixture B; 3) Molding the mixture A and the mixture B according to the contact material structure to obtain a loose compact; 4) Place the copper sheet into the mold, place the compact on the surface of the copper sheet with the diamond copper layer facing downward; 5) Preheat the mold in vacuum, pour molten copper into it, pressurize it so that the molten copper penetrates into chromium and diamond successively and welds with the copper sheet, cools to the aging precipitation temperature, keeps warm, and cools.

4. The preparation method according to claim 3, characterized in that: 1) In The proportion of electrolytic copper powder in the mixture A is 5-15wt%; and / or The particle size of the electrolytic copper powder is -200 mesh, and the particle size of the chromium powder is 300-100 mesh.

5. The preparation method according to claim 3, characterized in that: 2) In The proportion of electrolytic copper powder in the mixture B is 10-20wt%; and / or The particle size of the electrolytic copper powder is -200 mesh, and the particle size of the diamond powder is 600-200 mesh.

6. The preparation method according to claim 3 or 5, characterized in that: 2) In The grinding balls of the ball mill are tungsten balls; and / or The diameter of the tungsten ball is 1-5 mm, the ball-to-material ratio is 2-4:1, the ball milling speed is 30-45 rpm, and the time is 120-240 min.

7. The preparation method according to claim 3, characterized in that: 5), the vacuum degree of the vacuum preheating is 3-7×10 -2 Pa, temperature is 700-900℃, time is 10-30min.

8. The preparation method according to claim 3 or 7, characterized in that: 5), the temperature of the copper melt is 1200-1400°C.

9. The preparation method according to claim 3 or 7, characterized in that: 5), the pressurized pressure is 1-3 MPa.

10. The preparation method according to claim 3 or 7, characterized in that: 5), the aging precipitation temperature is 450-550°C, and the holding time is 60-120min.